Les fortifications endogenes au Senegal Oriental (17ème - 19ème siecle) - Aymeric Nsangou, Jacques (BAR International, 2022)
This book studies the archaeological remains of the endogenous fortifications of eastern Senegal during the Atlantic slave trade. In the first part, it deals with generalities by dealing with the determinants of the establishment of fortifications in West Africa. Following a proposed classification of endogenous West African fortifications, it gives an overview of the different types of fortifications present from Senegal to Cameroon. In the second part, it presents the military and political history of the state entities on the left bank of the Falémé (the Fulani kingdom of Boundou, and the Malinké kingdoms of Dantila, Sirimana, and Beledougou), as well as the defensive structures that have formed the basis of this story. As much as possible, each ruin of fortifications is studied under an archaeological and historical approach. Finally, the book examines the place of fortifications in the history of West Africa and their value as tangible cultural heritage.